2013
DOI: 10.1155/2013/713859
|View full text |Cite
|
Sign up to set email alerts
|

Hmgb1-IL-23-IL-17-IL-6-Stat3 Axis Promotes Tumor Growth in Murine Models of Melanoma

Abstract: In order to understand how tumor cells can escape immune surveillance mechanisms and thus develop antitumor therapies, it is critically important to investigate the mechanisms by which the immune system interacts with the tumor microenvironment. In our current study, IL-17 deficiency results in reduced melanoma tumor size, diminished numbers of proliferating cells and blood vessels, and decreased percentage of CD11b+Gr-1+ MDSCs in tumor tissues. IL-17 promotes IL-6 induction and Stat3 activation. Treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 44 publications
0
40
1
Order By: Relevance
“…IL-23 is an important cytokine in Th17 cell regulation. In contrast to our data, IL-23 has been shown to promote tumor progression and prevent anti-tumor immunity [ 31 ]. IL-23 produced by macrophages promotes tumor growth by activating STAT-3 in the macrophages and Treg cells [ 32 ].…”
Section: Discussioncontrasting
confidence: 99%
“…IL-23 is an important cytokine in Th17 cell regulation. In contrast to our data, IL-23 has been shown to promote tumor progression and prevent anti-tumor immunity [ 31 ]. IL-23 produced by macrophages promotes tumor growth by activating STAT-3 in the macrophages and Treg cells [ 32 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This finding was consistent with the results of a previous study (50); in this previous study, it was revealed that the expression of ICAM-1 is reduced by anti-IL-17. Similarly, another study suggested that HMGB1 can stimulate the expression of IL-17 (51). These results indicated that the HMGB1-IL-17-ICAM1 pathway has a critical role in the inflammatory response of PM.…”
Section: Discussionmentioning
confidence: 75%
“…Melanoma, also termed malignant melanoma, is a common skin neoplasm caused by hyperplasia of abnormal melanocytes (13). Although China is one of the countries with a low incidence of melanoma, the growth rate of malignant melanoma has continued to increase over previous years (14).…”
Section: Discussionmentioning
confidence: 99%